O TERRITÓRIO APA CANTÃO NO TOCANTINS E A POLÍTICA TERRITORIAL: UMA ANÁLISE A PARTIR DA TEORIA DO RECONHECIMENTO - Batista, Solange Ferreira (2018)
The purpose of this dissertation was to analyze the practices of the Territorial Collegiate, from the perspective of the Theory of Recognition. The theoretical dimensions proposed by Nancy Fraser and José Henrique de Faria were used in the categories of economic, social, political and emotional recognition of the APA Cantão Territory Collegiate of the State of Tocantins. For the accomplishment of the research, a field study was carried out with qualitative methodological basis. Data collection was done through documentary research in the year 2016 to 2017 and semi-structured interviews from August to September 2018, being analyzed based on social discourse theory. The results of this study reveal that the Territorial Collegiate favored the recognition of the individuals belonging to the APA Cantão Territory, under four categories analyzed, but also raise elements that show the lack of recognition of the population in some very specific cases. The research showed that with the creation of the College can be observed advances in social interaction between individuals, as well as the valuation of cultural practices, whether in the production of handicrafts, artisanal agro-industrialization and agro extractivism of the fruits of the cerrado, activities used for the generation of income with the active participation of the Women Committee, awakening in these subjects the feeling of belonging and of individual and collective identity. With the objective of analyzing the practices of the Territorial Collegiate, in the perspective of the political, social and emotional recognition of the individuals belonging to the APA Cantão do Tocantins territory, this one went further than in the conscious awakening of each subject in understanding and understanding that are agents of community change. This facilitated the parity participation of the discussions and resolution of problems of the population by the representatives of the Territorial Collegiate. As a whole, it can be said that the Collegiate is considered a basic instrument representative of collective order of community development, which has leveraged considerable advances in social development throughout the territory. However, it is considered that in terms of recognition and participation there is a long process is still under construction, and it is necessary to expand the subjects involved, such as ensuring the participation of populations living in remote communities, and this is a recent and under construction and that the Collegiate is still marked by several contradictions to be overcome.